Economic aspects of the relationship between state and people in the Caribbean - Bourne, Compton (UWI Port of SpainTT, 1986)
Describes characteristic activities of the people and state in three political relationships viz. the democratic-pluralist, authoritarian, and populist-statist. Discusses aspects of the State-People relationship in the democratic-pluralist system. Focuses particularly on the role of the state as a `patron' and as an agent of economic regulation. Outlines reasons for regulatory action and describes process or fate of regulations in democratic pluralist societies. Concludes that there is no correlation between the three types of political regimes and national economic performance and quality of life indicators.